The Jewish calendar controversy of 921/2 CE - Stern, Sacha 1962-; Rustow, Marina; Vidro, Nadia; Vollandt, Ronny 1978- (Leiden Boston BRILL, 2019)
"In the year 921/2, the Jewish leaders of Palestine and Babylonia disagreed on how to calculate the calendar. This controversy led to the celebration of Passover and other festivals, through two years, on different dates. Although the whole Jewish Near East was drawn into the controversy, it was later forgotten, until its 19th-century rediscovery in the Cairo Genizah. The faulty editions of these texts have led to much misunderstanding about the nature and aftermath of the controversy. In this book, Sacha Stern re-edits completely the texts, discovers many more, and challenges the consensus on the controversy's history. This book sheds light on medieval Rabbanite relations, and on the processes that brought about the standardization of the calendar in medieval Jewry."
Intro; ‎Contents; ‎Preface; ‎Figures, Plates and Tables; ‎Figures; ‎Plates; ‎Tables; ‎Abbreviations; ‎Editorial Policies, Manuscripts and Sigla; ‎Part 1. Introduction; ‎Chapter 1. The Controversy Revisited; ‎Chapter 2. Palestinians and Babylonians in Conflict: A Narrative; ‎Chapter 3. Discovery and Early Scholarship; ‎Chapter 4. Manuscripts, Texts, History: A New Approach; ‎Chapter 5. The Jewish Calendar: The Controversy Explained; ‎Part 2. The Book of the Calendar Controversy; ‎Chapter 6. The Book of the Calendar Controversy: Introduction
‎Chapter 7. The Book of the Calendar Controversy: Critical Edition‎Chapter 8. The Book of the Calendar Controversy: Diplomatic Editions; ‎Part 3. Letters and Polemics, c. 922CE; ‎Chapter 9. Ben Meir's First Letter; ‎Chapter 10. Saadya's Letters; ‎Chapter 11. Letters Miscellany; ‎Chapter 12. Babylonian Letter 1; ‎Chapter 13. Babylonian Letter 2; ‎Chapter 14. Discourse on the Midday Limit; ‎Chapter 15. Palestinian Polemic; ‎Part 4. Later Sources; ‎Chapter 16. Short References and Narratives (Sahl b. Maṣliaḥ, Hayye Gaon, Elias of Nisibis, and Various Genizah Sources)
‎Chapter 17. Palestinian Calendar Manuals‎Conclusion; ‎Glossary; ‎References; ‎Index of Sources; ‎Manuscripts; ‎Texts; ‎General Index; ‎Plates
Keywords: Cultural Studies; History; Jewish calendar; Sources; Middle East ; Babylonia